A novel homozygous variant in COX5A causes an attenuated phenotype with failure to thrive, lactic acidosis, hypoglycemia, and short stature. Issue 1 (9th March 2022) - Torraco, Alessandra; Morlino, Silvia; Rizza, Teresa; Di Nottia, Michela; Bottaro, Giorgia; Bisceglia, Luigi; Montanari, Arianna; Cappa, Marco; Castori, Marco; Bertini, Enrico; Carrozzo, Rosalba
Abstract: Genetic defect in the nuclear encoded subunits of cytochrome c oxidase are very rare. To date, most deleterious variants affect the mitochondrially encoded subunits of complex IV and the nuclear genes encoded for assembly factors. A biallelic pathogenic variant in the mitochondrial complex IV subunit COX5A was previously reported in a couple of sibs with failure to thrive, lactic acidosis and pulmonary hypertension and a lethal phenotype. Here, we describe a second family with a 11‐year‐old girl presenting with failure to thrive, lactic acidosis, hypoglycemia and short stature. Clinical exome revealed the homozygous missense variant c.266 T > G in COX5A, which produces a drop of the corresponding protein and a reduction of the COX activity. Compared to the previous observation, this girl showed an attenuated metabolic derangement without involvement of the cardiovascular system and neurodevelopment. Our observation confirms that COX5A recessive variants may cause mitochondrial disease and expands the associated phenotype to less severe presentations. Abstract :